Pengembangan Video Pembelajaran pada Model Problem Based Learning dengan Metode Scaffolding Materi Peluang Kejadian untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi - Didik, Sugiharto; Afifah, Dian Septi Nur; Setiani, Rahyu (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Schools are responsible for providing students with the skills needed to communicate ideas, analyze problems using complex data, respond to information, solve problems methodically, and use concepts and facts correctly. In reality, Indonesian students still have relatively low levels of advanced thinking skills. Program Results With a score of 379 for mathematics, 398 for science, and 371 for reading, Indonesia is ranked 68th in the 2022 International Student Assessment (PISA) announced on December 5, 2023. To improve critical thinking skills about reliable, practical, and efficient probability content, this study aims to test how effectively video content can be learned by utilizing the Problem-Based Learning model and scaffolding techniques. The research approach is based on the Borg and Gall paradigm. The product trial involved 34 grade X students from SMKN 2 Tulungagung. Data analysis techniques include paired t-tests (dependent sample t-tests), normality tests, and N-Gain calculations. The learning video was assessed as (1) very valid with an average percentage of 94.56%, (2) very practical with an average percentage of 95.05%, and (3) effective with Sig. value based on research findings. (2-tailed), especially 0.001 < 0.05, on the pre-test and post-test data pairs, indicating that H0 was rejected and H1 was accepted. The difference in the average scores of the pre-test and post-test indicated that the use of learning videos in the PBL model with the scaffolding method was proven to have an impact on improving students' high-level thinking skills regarding content on the probability of events.